PUSKESOS Information System to Support Poverty Management in South Pekon Wates Based on Pringsewu Regent Regulation Number 25 of 2020 - Tauzih, Asep; Mardeli, Iis (YHMM PUBLISHING, 2024)
This study aims to examine the implementation of Regent Regulation of Pringsewu No. 25 of 2020 on the Social Welfare Center (PUSKESOS) and to develop a web-mobile-based Puskesos Information System to enhance the effectiveness of social welfare services in Pekon Wates Selatan, Gadingrejo District, Pringsewu Regency. The system is designed to facilitate the verification and validation of the Integrated Social Welfare Data (DTKS) and to improve transparency in managing beneficiary information. The research employs observation, discussion, and village deliberation (Musdes) methods, using the waterfall model for system development. The results indicate that the developed system functions well, is user-friendly, and is well accepted by users. Its implementation contributes to improving data accuracy, operational efficiency, and the overall quality of public services while supporting the application of e-Government at the village level for effective and sustainable social welfare management.